PEMODELAN TLCL DAN TCCL UNTUK KOTA BANDUNG DENGAN MENGGUNAKAN METODE SKEW-T PLOTTING - Toni Samiaji (Lembaga Penerbangan dan Antariksa Nasional, 2004)
Simple model has been made to predict temperature of LCL and CCL based on surface on surface dew point data. The method which used is skew-T plotting, i.e. plotting temperature and dew point profile of radiosonde data on aerogram paper. The data which used is radiosonde sounding data of Bandung in 1992, 1995, 1997 and 1999. Model formula which obtained has linear form, when surface dew point straight proportional to LCL and CCL temperature. CCL and LCL temparature modelling based on surface humidity data has been made natural logarithmic of surface humidity. LCL temperature has good correlations to CCL temperature, and generally form linear and straight proportional.